Nitrogen Content of Leaves of Some Exotic and Indigenous Forest Tree Species Planted at New Forest - Puri, G. S. (Indian Forester, 1959)
Nitrogen plays an important role in the metabolism of plants. The fertility status of the soil is, therefore, closely related with its Nitrogen content. Foliar Nitrogen is an indication of the suitability of species for different sites for plantation purposes. Species with a high content of foliar Nitrogen improve the Nitrogen content of the top layer of the soil and the development of abundant ground flora further enriches it. With a view to build up our knowledge of foliar Nitrogen contents of indigenous as well as exotic species, leaves of 108 species were tested. The results are tabulated. Nitrogen content of the Gymnosperms is the lowest. Pongamia pinnata and Alnus nepalensis are the richest in Nitrogen.